2015
DOI: 10.1021/acs.est.5b01005
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immunoassay for the Detection of the Phenylpyrazole Insecticide Fipronil

Abstract: Phenylpyrazole insecticides such as fipronil have been used as replacements for organophosphates. The wide application of fipronil raises concern about environmental contamination and risk for fish, birds, other non-targeted beings and human health. A sensitive, competitive indirect heterologous enzyme-linked immunosorbent assay (ELISA) was developed. Antibodies with different specificities to fipronil and its metabolites were produced. Two ELISAs having IC50 values of 0.58 ± 0.06 and 2.6 ± 0.4 ng/mL were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 45 publications
0
71
0
1
Order By: Relevance
“…We previously developed 2 immunoassays using different sera for the detection of fipronil (Vasylieva et al 2015b). Cross-reactivity (CR) to hydroxy-fipronil was tested with these polyclonal antibodies 2265 and 2268 (pAbs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously developed 2 immunoassays using different sera for the detection of fipronil (Vasylieva et al 2015b). Cross-reactivity (CR) to hydroxy-fipronil was tested with these polyclonal antibodies 2265 and 2268 (pAbs).…”
Section: Resultsmentioning
confidence: 99%
“…S5). The assay 2268 is more robust to changing sample conditions like pH or ionic strength (Vasylieva et al 2015a). We therefore chose this assay to assess the applicability of the immunoassay for screening of urine samples for the presence of biomarkers of exposure to fipronil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the pAB could simultaneously recognize TBBPA DHEE and TBBPA MHEE, manifesting low cross-reactivity to the other selected compounds. Meanwhile, although a linker arm of 3e5 carbon atoms was generally considered an optimal distance between hapten and the carrier protein (Vasylieva et al, 2015), our hapten design showed that linker arms of less than 3 also met the requirements for generating the antibodies.…”
Section: Preparation Of Hapten M3 Its Conjugates and Antibodymentioning
confidence: 92%
“…Since TBBPA-DHEE belongs to a nonpolar chemical, methanol is useful to keep the hydrophobic targets in immunoassay solution and prevent nonspecific binding on the container walls (Vasylieva et al, 2015). In order to improve the performance of the ELISA method, methanol was added to the assay system.…”
Section: Optimization Of Elisa Conditionsmentioning
confidence: 99%